Amplify your efforts in higher education to create long‐lasting social change. Issue 7 (23rd February 2021) - Sutton, Halley
Abstract : Julie Coonrod, Ph.D., Dean of Graduate Studies at the University of New Mexico, was born and raised in Albuquerque. "I absolutely love everything about this place, " Coonrod said, adding that she's spent 25 years at the institution.